THU0429 Ultrasound Differences Between Psoriatic Onychopathy and Onychomycosis. (9th June 2015) - Moreno, M.; Lisbona, M.; Luelmo, J.; Gallardo, F.; Ferran, M.; Pontes, C.; Vives, R.; Gratacόs, J.; Maymo, J.
Abstract : Background: Psoriatic onycopathy in oil drop with or without onicholysis is an entity that can be difficult to distinguish from onychomycosis. Previous studies with ultrasound nail described findings that might be useful in the differential diagnosis in early-onset arthritis cohorts Objectives: Determine whether there are ultrasound differences (quantitative or qualitative) between psoriatic onychopathy and onychomycosis. Methods: Transversal study with consecutive inclusion of patients with onychopathy in oil drop during 2 years. We studied 3 groups: 1. Patients with onychomycosis confirmed by nail culture; 2. Patients with psoriatic onychopathy (with o without arthritis) and mycotic culture negative and 3. Healthy controls. We registered demographic variables (age, gender), NAPSI most affected nail in groups 1 and 2, quantitative ultrasound parameters grey scale collected: thickness in millimeters (mm) of the interplate distance and nail bed in longitudinal and transverse distance in mm between the germinal matrix and the cortex of the distal phalanx and extensor tendon thickness longitudinal; qualitative ultrasound parameters grayscale: triband morphology of the nail plate, morphological alterations of the nail plate (Types I-IV of Wortsman X et al.), presence of signal power Doppler (PD) of nail bed (graded on a scale of 0-3) and the digital extensor tendon entheses (gradient 1: present and 2: absent) After the ultrasound examination nail sample for culture in Sabouraud Agar was collected. A color Doppler equipment (ESAOTE Mylab 60) was used with 7-13 MHz linear probe. To study reliability intraclass correlation coefficients (ICC) interobserver of the first 16 patients enrolled from 2 sonographers (MPL and MMM) were calculated blind diagnosis. Results: 110 patients were included. Finally 78 patients were analyzed (47 women, median age 50.4±10.8 years), 25 with onychomicosis, 35 with psoriatic onychopathy (24 psoriatic arthritis and 11 psoriasis without arthritis) and 18 healthy controls. Patients with psoriatic onychopathy presented regarding the group with onychomycosis a smaller thickness of the nail plate and nail bed as well as a higher frequency signal nail bed PD ≥2 (60% vs 16%, p=0.006). The presence of ultrasonographic synovitis of the DIP joint corresponding to the nail study was infrequent and no significant difference between psoriatic onychopathy and onychomycosis (on 8 and 5 patients, respectively), however in psoriatic onychopathy a higher prevalence was observed structural lesions in the DIP joint of the finger affection when compared with onychomycosis (22 vs 2 patients, p<0.001). Finally, the prevalence and severity according NAPSI of onychomycosis in the hands was statistically lower when compared with psoriatic onychopathy. Conclusions: These results suggest a potential use of nail ultrasound in the differential diagnosis of psoriatic onychopathy and onychomycosis, however, more studies with larger sample size and better resolution of ultrasound machines are necessary for confirm these findings. Disclosure of Interest: None declared